Halal Certification of Indonesian Cosmetics Products: New Protectionism and the Rise of Islamic Populism in Indonesia - Bachtiar, Farahdiba Rahma (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
This article aims to explore the impact of halal certification of Indonesian products and the interplay between halal certification, Indonesia’s economic interest and International Trade Regime. This research uses qualitative approach taking Indonesia case study by collecting secondary data from varied sources. The findings indicate that the massive awareness of halal products especially cosmetic is not solely motivated by religious motive. The halal product is not substantially driven by religiosity. In fact, to understand the meaning of halal, this paper argues that companies that trade halal product do not follow Islamic values. Further, this paper suggests that Islam does not support economic system that prioritizes a few parties, put women as an object, not environmentally friendly, or wasteful. On the contrary, it promotes an order that is not fair for all. However, this paper further argues that halal trend in Indonesia trade system is more about the rise of Islamic populism. WTO therefore, has to be cautious on accommodating halal labelling in international trade. It must be opened to the needs of Islamic countries yet it has to be aware that it may become new form of protectionism which is unfair for global trade standards.